Identification of peptides with high red blood cell and hepatocyte binding activity in the Plasmodium falciparum multi-stage invasion proteins: PfSPATR and MCP-1 (2008)
Plasmodium falciparum multi-stage proteins are involved in vital processes for parasite survival, which turns them into attractive targets for studies aimed at developing a fully effective antimalarial vaccine. MCP-1 and PfSPATR are both found in sporozoite and merozoite forms, and have been associated respectively with invasion of hepatocytes and red blood cells (RBCs). Binding assays with synthetic peptides derived from these two important proteins have enabled identifying those sequences binding with high specific activity (named High activity binding peptides-HABPs) to hepatoma-derived HepG2 cells and human RBCs. Twelve RBC HABPs were identified within the MCP-1 amino acid sequence, most of them in the C-terminal region. The MCP-1 HABPs 33387 and 33397 also presented high activity binding to HepG2 cells. PfSPATR presented four RBC HABPs and two HepG2 HABPs, but only one (32686) could bind to both cell types. RBC binding assays evidenced that binding of all HABPs was saturable and differentially affected by the enzymatic treatment of target cells. Moreover, all HABPs inhibited in vitro invasion of merozoites at 200 ?M and had particular structural features when analyzed by circular dichroism. The results suggest that these synthetic peptides capable of binding to the two P. falciparum target cells could be potentially included in the design of a multi-stage, subunit-based, chemically synthesized antimalarial vaccine. © 2008 Elsevier Masson SAS. All rights reserved.